Visible-light responsive novel WO3/TiO2 and Au loaded WO3/TiO2 nanocomposite and wastewater remediation: Mechanistic inside and photocatalysis pathway. (August 2020) - Rhaman, Md. Masudur; Ganguli, Sumon; Bera, Sandipan; Rawal, Sher Bahadur; Chakraborty, Ashok Kumar
Graphical abstract: Highlights: Visible-light active (λ ≥ 420 nm) WO3 /TiO2 composite was prepared utilizing cis -butenedioic as a sharing molecule. Au-WO3 /TiO2 has been synthesized and Au nanoparticles were homogeneously deposited on to surface of WO3 /TiO2 nanojunction. Both the prepared composites are highly effective to degrade organic pollutants from industrial wastewater. A possible degradation mechanism of organic pollutants with the composites has been established. Abstract: Global environmental pollution is thought to be the principal source of emission of industrial untreated effluent. Photocatalysis is the versatile process to eliminate these pollutants which is utilizing semiconductor metal oxides. A nanocomposite WO3 /TiO2 working under visible-light (λ ≥ 420 nm) has been prepared employing cis -butenedioic acid to associate component semiconductors of WO3 and TiO2 nanoparticle. The composite was optimized to 5 mol% WO3 /TiO2 in terms of photocatalytic activity to decompose phenol and methylene blue dye in aqueous under visible-light. Afterwards, Au nanoparticle was deposited on to the surface of optimized WO3 /TiO2 . Au loaded WO3 /TiO2 were characterized by scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray diffraction (XRD), energy-dispersive X-ray spectroscope (EDX) mapping and UV–vis absorption spectra. Photocatalytic efficiency of Au-WO3 /TiO2 has been measured to degrade above organic pollutants in aqueous phase under visible-light. Au-WO3 /TiO2 demonstrated extraordinarily high photocatalytic efficiency in decomposing the pollutants compare to 5 mol% WO3 /TiO2 nanocomposite. After 120 min of visible irradiation, 63 % decomposition of phenol and 52 % degradation of methylene blue dye was observed under the identical condition. The outstanding improvement of photocatalytic efficiency of Au-WO3 /TiO2 nanocomposite ascribed due to the perfect matching of energy band positions of WO3 and TiO2 which inhibit photo-excited (e‾)–hole (h + ) recombination as well as favor inter particle transfer between WO3 and TiO2 . Au nanoparticles enhances transfer of electron (e‾) from CB of WO3 . Thus, possible recombination of photo-excited electron (e‾)–hole (h + ) pair was retarded and photocatalytic efficiency was greatly improved.